2020
DOI: 10.3390/ijms21249335
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Angiogenesis in the Most Common Salivary Gland Malignant Tumors

Abstract: Salivary gland carcinomas (SGCs) represent a group of rare tumors, with complete surgical resection being the main treatment option. Therapeutic armory for cases of locally aggressive, recurrent, and/or metastatic SGCs, though, remains poor since they exhibit high rates of resistance to systematic therapy. Angiogenesis is considered one of the contemporary hallmarks of cancer and anti-angiogenic factors have already been approved for the treatment of several cancer types. This review aims to summarize, in a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 66 publications
1
1
0
5
Order By: Relevance
“…9,24 The primary element affecting vascular density in macroscopic tumours is the metabolic requirement, which usually increases with tumour growth. 25,26 In the current study, salivary and laryngeal ACC vasculature generally formed a ring of capillaries surrounding tumour nests and stained positively in a solid pattern rather than in a cribriform or tubular pattern. The present study agrees with Moghadam, et al (2015) 27 , who found that SACC vasculature commonly formed a capillary ring surrounding tumour nests.…”
Section: Discussionsupporting
confidence: 45%
“…9,24 The primary element affecting vascular density in macroscopic tumours is the metabolic requirement, which usually increases with tumour growth. 25,26 In the current study, salivary and laryngeal ACC vasculature generally formed a ring of capillaries surrounding tumour nests and stained positively in a solid pattern rather than in a cribriform or tubular pattern. The present study agrees with Moghadam, et al (2015) 27 , who found that SACC vasculature commonly formed a capillary ring surrounding tumour nests.…”
Section: Discussionsupporting
confidence: 45%
“…PI3K signaling is usually intensified by the loss of function of the negative regulation of PTEN, whose main substrate is PIP3, thus enhancing the activation of AKT [ 84 , 85 ]. Correspondingly, several studies denote VEGF in respect to the tumor microenvironment (TME) as a prognostic factor commensurate with tumor size, aggressive behavior and metastasis, and cell growth [ 85 , 86 , 87 ]. Basically, TME is characterized by heterogeneous, aberrant vasculature derived from an imbalance among pro- and non-angiogenic factors [ 88 , 89 ].…”
Section: Angiogenetic Behavior As a Consequence Of Pc/ec Crosstalkmentioning
confidence: 99%
“…El crecimiento de un tumor, la invasión y las metástasis dependen de la angiogénesis, que es una característica distintiva del cáncer [10][11] . El método más común para evaluar la actividad de angiogénesis consiste en medir la cantidad de vasos en un tumor, lo que nos da una estimación de la densidad microvascular 11 . Para evaluar la angiogénesis se utilizan distintos marcadores, como CD34, CD31, CD105 (endoglobin) y VEGF (vascular endothelial growth factor) 11 .…”
Section: Introductionunclassified
“…El método más común para evaluar la actividad de angiogénesis consiste en medir la cantidad de vasos en un tumor, lo que nos da una estimación de la densidad microvascular 11 . Para evaluar la angiogénesis se utilizan distintos marcadores, como CD34, CD31, CD105 (endoglobin) y VEGF (vascular endothelial growth factor) 11 .…”
Section: Introductionunclassified